1974
DOI: 10.1002/chin.197415049
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: THE KINETICS OF HYDROGEN ABSORPTION IN PALLADIUM (ALPHA‐ AND BETA‐PHASE) AND PALLADIUM‐SILVER‐ALLOYS

Abstract: The reaction H2 → 2 H (dissolved) on thin Pd and Pd‐Ag foils (2.5–5 μm) was studied, with the aid of resistance measurements, in a flow apparatus at temperatures in the range 20–150°C. The rate determining step is the dissociation of the H2‐molecule on the metal surface. It is assumed that in the formation of the activated complex one atom (proton) already enters an interstitial site in the lattice. For very low hydrogen concentrations xH in α‐phase Pd and in Pd‐Ag alloys, where Sieverts law applies, the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 3 publications
4
22
1
Order By: Relevance
“…To the best of author's knowledge, the kinetics of PdeAg alloy foil in the bi-phasic (a þ b) region is not reported in the literature for direct comparison. However, the activation energy of hydrogen absorption by Pd 0.77 Ag 0.23 obtained in the present study is considerably lower compared to both the literature values reported for single phase region of pure palladium and PdeAg alloys [24,25]. Since, kinetic data depends on many factors like method of measurement, sample size and shape, surface impurity and heat treatment; it is apparently difficult to compare results obtained by different authors.…”
Section: Kinetic Considerationscontrasting
confidence: 70%
See 1 more Smart Citation
“…To the best of author's knowledge, the kinetics of PdeAg alloy foil in the bi-phasic (a þ b) region is not reported in the literature for direct comparison. However, the activation energy of hydrogen absorption by Pd 0.77 Ag 0.23 obtained in the present study is considerably lower compared to both the literature values reported for single phase region of pure palladium and PdeAg alloys [24,25]. Since, kinetic data depends on many factors like method of measurement, sample size and shape, surface impurity and heat treatment; it is apparently difficult to compare results obtained by different authors.…”
Section: Kinetic Considerationscontrasting
confidence: 70%
“…The kinetics of hydrogen absorption in palladium and PdeAg alloys have been studied by Auer and Grabke [24] with the aid of resistance measurements in a flow apparatus in the temperature ranges 293e423 K. However, they have reported the kinetic data only for the single phase regions and concluded that the rate determining step is the dissociation of the H 2 molecule on the metal surface. The activation energy for hydrogen absorption reaction is 28.5 kJ/mol H 2 for pure palladium and in the range of 29.3e37.6 (kJ/mol H 2 ) for Pd 1Àz Ag z (z ¼ 0.1e0.4).…”
Section: Kinetic Considerationsmentioning
confidence: 98%
“…3(a) ). It can be seen that for both samples the data initially follow Sievert's law [1] characteristic of the α phase of PdH x , i.e. a linear relationship, before deviating from it for ffiffiffiffiffiffiffi P H 2 p in excess of 50.4 Pa 1/2 (or P H 2 ≈ 2.54 × 10 3 Pa).…”
Section: Resultsmentioning
confidence: 90%
“…With PdH x in the α phase, the absorbed H concentration n follows Sievert's law n = AP H 2 1/2 , where P H 2 is the hydrogen partial pressure and A is a proportionality constant. As P H 2 increases, interactions between absorbed H atoms cause deviations from Sievert's law [1] typically for pressures above 2.7 × 10 3 Pa at room temperature. The β-phase of PdH x is characterised with a saturation of the hydrogen concentration n with increasing H pressure following the expansion of the Pd lattice (α + β transition phase).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation